Sistematización de procedimientos para fiscalizar la planificación, ejecución y control de obras viales. - Vargas-Duarte, Andrea (Instituto Tecnológico de Costa Rica, 2010)
The work focuses on Municipal Road Management and control processes performed specifically in bituminous surface treatment, asphalt patching and bridges construction. The main objective of this work was the systematization of the control processes carried out by Internal Audit of Pérez Zeledón (MPZ) for the aforementioned works. To achieve the main objective was necessary to diagnose the current situation on MPZ works, which was achieved through personal interviews and the application of guides. Then was performed of the different processes by developing a risk matrix. Having identified the risks , a tool was a developed that facilities the control processes based on identified risks. The tool was the end result and consisted of a manual with instruments that can evaluate performance in implementing each of the works cited. Finally, the tool was implemented by evaluating three projects by the MPZ. This research confirmed the responsibility of the Engineer in charge of the works, and the importance of his/her painstaking work, through efficient process planning, inspection and quality control of each work. The results confirmed that the Municipal Road Management can and need to be improved, to achieve a true development on road infrastructure, however it requires a cultural change where the Road Management become more than a political commitment turning into real planning and high quality works, which will endure over time.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2010.
Keywords: Tratamiento; Carretera; Bacheo; Gestión; Diagnóstico